Cow Urine for Enhancement of Biogas Production and Fertilizer Quality of Biogas Slurry - Fardous, M. R.; Nasrin, M. S.; Shakil, M. E.; Islam, M. S.; Hoque, M. A.; Islam, M. N. (Journal of Scientific Research, 2020)
To explore the potency of cow urine on biogas production and fertilizer quality of the biogas slurries, six experimental trials, T0 (50% CD:50% Water) as control, T1 (10% CD:90% CU), T2 (20% CD:80% CU), T3 (30% CD:70% CU), T4 (40% CD:60% CU) and T5 (50% CD:50% CU) were constructed by mixing cow dung (CD) and cow urine (CU). Cumulative gas volume was estimated for 30 days and the physicochemical properties of the slurries were evaluated. The cumulative gas volume of three trials (T3, T4 and T5) was higher than control (T0) and T5 showed maximum (28% over the control). Moreover, all of the trials except one (T1) showed higher gas yield than control (T0) of which maximum conversion of volatile solid (VS) to gas was obtained in T3. pH of the amended samples were above 7.0 (pH 7.00-7.42). Conductivity of the samples also increases (1.94-13.40 mS cm-1) with the increase in cow urine percentage. With respect to macronutrient (N, P, K) cow urine amended samples can be considered superior to the control one. Moreover, C/N ratio of all the amended samples were below 15 (4.7-14.0) and thus these are suitable for agronomic uses.